2005
DOI: 10.1542/peds.2005-0147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Low-Allergen Maternal Diet on Colic Among Breastfed Infants: A Randomized, Controlled Trial

Abstract: ABSTRACT.Background. There is controversy regarding whether hypersensitivity to food proteins contributes to colic among breastfed infants.Methods. A randomized, controlled trial of a lowallergen maternal diet was conducted among exclusively breastfed infants presenting with colic. In the active arm, mothers excluded cow's milk, eggs, peanuts, tree nuts, wheat, soy, and fish from their diet; mothers in the control group continued to consume these foods. Outcomes were assessed after 7 days, as the change in cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0
9

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(98 citation statements)
references
References 46 publications
0
88
0
9
Order By: Relevance
“…In nutritional interventions, a significant difference was found just in the type of infant's feeding (breastfeeding more than formula feeding) [12]. Hill et al demonstrated via an RCT that elimination of certain allergenic foods (cow milk, soy, wheat, eggs, peanuts, tree nuts, and fish) was positively associated with a reduction in infantile colic in breastfed infants [13]. In chemical drugs consumption, a significant difference was found between the two groups regarding birth order, milk getting information, family income and mother's education level.…”
Section: Discussionmentioning
confidence: 99%
“…In nutritional interventions, a significant difference was found just in the type of infant's feeding (breastfeeding more than formula feeding) [12]. Hill et al demonstrated via an RCT that elimination of certain allergenic foods (cow milk, soy, wheat, eggs, peanuts, tree nuts, and fish) was positively associated with a reduction in infantile colic in breastfed infants [13]. In chemical drugs consumption, a significant difference was found between the two groups regarding birth order, milk getting information, family income and mother's education level.…”
Section: Discussionmentioning
confidence: 99%
“…15 A later randomised controlled trial by the same author in exclusively breastfed infants showed that a low-allergen maternal diet (excluding milk, eggs, nuts, wheat, soy and fish) significantly reduced infant crying compared with infants of mothers who continued to eat those foods. 16 In another randomised double-blind trial, a hydrolysed whey formula significantly reduced crying time by 58 minutes per day (p=0.03) compared with standard cow's milk formula. 17 The effect of physical interaction with infants on colic symptoms has also been investigated.…”
Section: Interventions That May Be Usefulmentioning
confidence: 98%
“…Cry/fuss duration per 48 hours was reduced by a substantially greater amount in the low-allergen group; the adjusted geometric mean ratio was 0.79, ie an average reduction of 21%. Mothers' subjective assessments of the responses to diet indicated little difference between the groups 16 Probiotics Lactobacillus reuteri improved colicky symptoms in breastfed infants within one week of treatment compared with simeticone or placebo; 95% were responders in the probiotic group 23 Sucrose solution Benefit reported in two trials. Sucrose effective for only a short period of time -effects lasting between 3 and 30 minutes 13 Hydrolysed whey formula versus standard cow's milk formula Infantile colic l PRESCRIBING IN CHILDREN ■ on reduction of colic symptoms.…”
Section: Interventions That May Be Usefulmentioning
confidence: 99%
“…Pored nasledne i razvojne sklonosti neadekvatnoj imunskoj reakciji na antigene hrane, u dodatne faktore rizika za pojavu ovog patološkog stanja spadaju urođeni deficit IgA, rođenje carskim rezom, dohrana ili veštačka ishrana u ranom neonatalnom periodu, ishrana neadaptiranim kravljim mlekom u dojenačkoj dobi, prerano ili suviše kasno uvođenje nemlečne hrane, če-ste gastrointestinalne infekcije u najranijem uzrastu i deficit vitamina D [4-6, 11, 14-16]. Senzibilizacija na komponente hrane, proteine i nekad haptene, najčešće nastaje direktnim putem, ali je moguća i posredstvom majčinog mleka, pa čak i transplacentalno [1,15,[17][18][19][20]. Sklonost neadekvatnoj imunskoj reakciji na antigensku stimulaciju je neselektivnog karaktera, te je nutritivna alergija često multipla i u visokom procentu udružena sa inhalacionom i/ili kontaktnom hipersenzitivnošću [21,22].…”
Section: Uvodunclassified